Edukasi Pentingnya Makanan Bergizi Dan Memilih Jajanan Sehat Bagi Anak Usia Sekolah - Muhammad Iqbal S; Nanda Desreza; Susi Handa Resta (Lembaga Pengembangan Kinerja Dosen, 2023)
School age is a period when parents need to maintain and pay attention to good weight growth. Therefore parents should pay attention to nutritious food in children. Carbohydrates, proteins and fats are macro-nutrients that need to be balanced every day. Nutritional problems in children are still a problem in Indonesia, such as thin children, stunting and anemia. Malnutrition will have an impact on the productivity and quality of life of children in the future. Data from the Kuta Baro Health Center showed that there were 22 children with malnutrition status. The purpose of community service is to increase mothers' knowledge and skills in serving and choosing healthy snacks for children. The service method is carried out through health education about nutritional needs and healthy snacks for school-age children as an effort to increase mothers' understanding of nutritional needs. The results showed that the participants were enthusiastic in participating in counseling and demonstrating choosing healthy snacks, indicated by the number of questions from the participants. After this service activity, it is hoped that parents can continue to provide nutritious food and children can choose healthy snacks so that together they can prevent children from being malnourished from an early age.